2019
DOI: 10.3389/fphys.2019.00434
|View full text |Cite
|
Sign up to set email alerts
|

The Sensory Machinery of the Head Louse Pediculus humanus capitis: From the Antennae to the Brain

Abstract: Insect antennae are sophisticated sensory organs, usually covered with sensory structures responsible for the detection of relevant signals of different modalities coming from the environment. Despite the relevance of the head louse Pediculus humanus capitis as a human parasite, the role of its antennal sensory system in the highly dependent relation established with their hosts has been barely studied. In this work, we present a functional description of the antennae of these hematophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…1A). Already described on the HL antenna (Ortega Insaurralde et al ., 2019), the single pore was observed for the first time in the BL. The single pore consists of a pit located on the flagellomere 3 (Fig.…”
Section: Description Of the Flagellar Bl Sensory Structuresmentioning
confidence: 90%
See 4 more Smart Citations
“…1A). Already described on the HL antenna (Ortega Insaurralde et al ., 2019), the single pore was observed for the first time in the BL. The single pore consists of a pit located on the flagellomere 3 (Fig.…”
Section: Description Of the Flagellar Bl Sensory Structuresmentioning
confidence: 90%
“…1C,D). Based solely on morphological and behavioural studies of the HL, finger‐like and sharp‐end basiconica were suggested to have an olfactory role, whereas the round‐end basiconica would accomplish a gustatory role, although functional studies are necessary to confirm these hypotheses (Ortega Insaurralde et al ., 2019).…”
Section: Description Of the Flagellar Bl Sensory Structuresmentioning
confidence: 99%
See 3 more Smart Citations